The concept of a certain forensic technique and its types - S. O. Knizhenko (Bulletin of Kharkiv National University of Internal Affairs)
The forensic technique is one of the sections of forensic science which task is to develop recommendations for the effective investigation of certain types of crimes. Nowadays there is no consensus among scholars about the concept of a certain forensic technique, its types, structure and tasks.